Modelling on seasonal lake ice evolution in central Asian arid climate zone: a case study - Peng, Lu; Cheng, Bin; Leppäranta, Matti; Zhijun, Li (Polar Research Institute of China - PRIC, 2021)
The seasonal cycle of ice thickness and temperature in Lake Wuliangsuhai, a typical shallow lake in the central Asian arid climate zone, was simulated using the HIGHTSI model and the MERRA-2 data as the meteorological forcing. The average ice growth rate was 0.64 cm·d−1 and −1.65 cm·d−1 for the growth and melting stage of the ice cover, respectively. The ice thickness agreed well with the field observations conducted in winter 2017, with a correlation coefficient of 0.97. The ice temperature field also agreed with observations in both daily variations and the vertical profile, and a better agreement in the daily amplitude and profile shape of ice temperature could be achieved if field data on physical properties of snow cover and melting ice were available. This study proved the feasibility of both the HIGHTSI model and the MERRA-2 data for modeling the ice cover evolution in Lake Wuliangsuhai, providing a basis for a deep insight into the difference of lake ice evolution between central Asian arid climate zone and polar/sub-polar regions.